Does the vicinity of the Black-Headed Gull colony (Chroicocephalus ridibundus) increase the breeding success of the Common Tern (Sterna hirundo) on the islands of the middle Vistula? - Dariusz Bukackiński; Monika Bukacińska; Milena Grabowska (Studia Ecologiae et Bioethicae)
We conducted our study in the Common Tern colony (STH) located on an island in the middle Vistula River course, at the height of the city of Dęblin (km 393–394 of the waterway), in 2017. Our goal was to investigate some aspects of the biology and reproductive ecology of this species. Due to the fact that STH breeds both in single-species as well as in two- or multi-species colonies, in associations with Little Terns (Sternula albifrons), Black-Headed Gulls (Chroicocephalus ridibundus) (LAR) and/or Mew Gulls (Larus canus), we wanted to investigate whether the neighborhood of other species (in this case LAR) affected hatching success and chick survival in STH. Our results clearly show that the presence of breeding terns in the neighborhood of the LAR colony was not accidental and/or caused by the lack of space on the island and/or the possibility of nesting elsewhere. The height of nesting site, type of nesting habitat, clutch size, mean egg volume and mean egg mass of these STH pairs did not differ significantly from those that formed a single species colony, on the same island but several hundred meters away. However, STH nests in the neighborhood of the LAR colony were established much earlier and both the hatching success and chick survival of STH during the early-chick stage were twice as high. Thus, we can conclude that the LAR colony could provide an effective protection against predation of crows, magpies and gulls, dangers which accounted for the vast majority of STH nest failures in the year of our study.